Serbia and France: the special relationship? - Varga-Kocsicska, Aleksandra (European Scientific Journal, ESJ, 2022)
What is the relationship between the European Union and the Western Balkans, and Serbia in particular? The author reviews the process of accession of the Western Balkan countries (with a focus on Serbia) to the European Union, but also the geopolitical stakes in this region, which is sought after by external actors such as China and Russia, and which the European Union should pay more attention in order to strengthen its strategic autonomy. The EU needs to take a bold stance in the Western Balkans and France wants to be at the forefront. European actors must show future member states that the door to full membership is indeed open, but only if they can truly embrace democratic values. In his analysis, the author writes about Serbia’s path towards EU integration through an increasingly close relationship with France. The current situation in Serbia is rather complex. Will it continue with its "hamster in the wheel" approach, where the result is always expected to be the same, or should Serbia adopt a different approach for the future? As concerns Serbia, France will certainly continue to insist on economic cooperation and the improvement of French investments in Serbia. They will also take a stand against damaging foreign influences which they believe could potentially destabilize the region and are fundamentally at cross purposes with the policy favored by the European Union.